Koagulasi Intravaskuler Diseminata pada Kanker - ANDREE KURNIAWAN; NATA PRATAMA HARDJO LUGITO (Indonesian Journal of Cancer, 2015)
Disseminated Intravascular Coagulation is one of thrombosis manifestation other than venous thromboembolism, which onset is acute and has slight different clinical manifestation that tends to be chronic. Pathogenesis of the DIC in hematology malignancy is caused by the activation of fibrinolytic pathway by tumor cells. In solid tumor the pathogenesis is mainly because of the activation of cogulation factor by tissue factor expressed by tumor cells. Thediagnosis of DIC in cancer still needs further validation from the international society of thrombosis and hemostasisand Japanese society hematology criteria in cancer subjects. The principle of therapy for DIC in cancer patients is management of the cancer itself as the underlying etiology with the target is remission. The uses of anticoagulant therapy needs further clinical trial in the future. Coagulation factor and platelet transfusion can be given if there is significant bleeding.Koagulasi intravaskuler diseminata (KID) adalah manifestasi trombosis lain selain tromboemboli vena yang bersifat akut. Pada pasien kanker gambarannya sedikit berbeda, yaitu cenderung bersifat kronik, tergantung pada jenis kankernya. Patogenesis KID pada keganasan hematologi adalah akibat fibrinolisis yang meningkat. Sedangkan pada tumor solid terjadi akibat aktivasi faktor koagulasi oleh faktor jaringan yang diekspresikan oleh sel kanker. Diagnosis KID pada kanker masih memerlukan validasi kriteria dari perhimpunan trombosis hemostasis internasional dan Jepang pada kelompok pasien kanker. Prinsip terapi KID pada kanker adalah tata laksana kanker yang menjadi penyebab, dengan target remisi penyakit. Pemberian antikoagulan memerlukan uji klinis menggunakan populasi pasien kanker. Transfusi faktor koagulasi dan atau trombosit hanya diberikan apabila terdapat perdarahan yang bermakna.